Development of Technology and Ballistic Research of the Propulsion Unit for 122 mm Rocket Missile with an Extended Range - Bogdan FLORCZAK; Andrzej CHOLEWIAK; Marek BIAŁEK (Problemy Mechatroniki, 2015)
The paper presents the results of ballistic studies on the demonstrator missile 122 mm rocket motor of an extended range with the heterogeneous solid propellant. The technology for producing the solid propellant can be deployed in the defense industry plants and used for the production of rocket motors for various purposes.